Geobacter Protein Nanowires - Lovley, Derek R.; Walker, David J. F. (Frontiers in Microbiology, 2019)
The study of electrically conductive protein nanowires in Geobacter sulfurreducens has led to new concepts for long-range electron extracellular transport, as well as the development of sustainable conductive materials and electronic devices with novel functions. Until recently, electrically conductive pili (e-pili), assembled from the PilA pilin monomer, were the only known Geobacter protein nanowires. However, filaments comprised of the multi-heme c-type cytochrome, OmcS, are present in some preparations of G. sulfurreducens outer-surface proteins. The purpose of this review is to evaluate the available evidence on the in vivo expression of e-pili and OmcS filaments and their biological function. Abundant literature demonstrates that G. sulfurreducens expresses e-pili, which are required for long-range electron transport to Fe(III) oxides and through conductive biofilms. In contrast, there is no definitive evidence yet that wild-type G. sulfurreducens express long filaments of OmcS extending from the cells, and deleting the gene for OmcS actually increases biofilm conductivity. The literature does not support the concern that many previous studies on e-pili were mistakenly studying OmcS filaments. For example, heterologous expression of the aromatic-rich pilin monomer of G. metallireducens in G. sulfurreducens increases the conductivity of individual nanowires more than 5000-fold, whereas expression of an aromatic-poor pilin reduced conductivity more than 1000-fold. This more than million-fold range in nanowire conductivity was achieved while maintaining the 3 nm diameter characteristic of e-pili. Purification methods that eliminate all traces of OmcS yield highly conductive e-pili, as does heterologous expression of the e-pilin monomer in microbes that do not produce OmcS or any other outer-surface cytochromes. Future studies of G. sulfurreducens expression of protein nanowires need to be cognizant of the importance of maintaining environmentally relevant growth conditions because artificial laboratory culture conditions can rapidly select against e-pili expression. Principles derived from the study of e-pili have enabled identification of non-cytochrome protein nanowires in diverse bacteria and archaea. A similar search for cytochrome appendages is warranted. Both e-pili and OmcS filaments offer design options for the synthesis of protein-based ‘green’ electronics, which may be the primary driving force for the study of these structures in the near future.